EVIDENCE OF ADDITIONAL LAYER FORMATION IN THE LOW LATITUDE IONOSPHERE - Sarmoko Saroso (Jurnal Sains Dirgantara, 2004)
Ionogram recorded from four ionosonde stations are employed to study the accurrence of an additional layer at F-region altitudes during 1-15 March 1998. It was found that the appearance of the additional layer at the local noontime hours is a typical phenomenon at Parepare (4˚S geographic, 14.8˚S geomagnetic) and Manila (3.7˚N geomagnetic), and was not observed at Chung-Li (14.2˚N geomagnetic). Furthermore, the additional layer was nor seen from any indicate that the fountain effect plays an important role in the formation of the additional layer. However, they also suggest the dynamics of the layer formation are in some way influenced by the location of the station relative to the geographic aquator.